Activity of Tri-N-Butyl Tin maleate in carpets against Staphylococcus aureus and Aspergillus niger, verified through two methodologies: Inhibition Halo (HZ) and Inhibition Surface (Print) Atividade de tri-n-butyl tin maleate em carpetes contra Staphylococcus aureus e Aspergillus niger, verificada através de duas metodologias: Zona de Inibição (ZI) e Superfície de Inibição (Impressão) - Satiko Uehara; Marcia Regina Franzolin; Flávio César Viani; Soledad Chiesa; Aricelma Pinheiro França; Claudete Rodrigues Paula (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
The aim of the present study was to verify the activity of the Tri-N-Butyl Tin maleate compound against Staphylococcus aureus and Aspergillus niger, after its industrial application in 40 samples of carpets of different materials (polypropylene, polyester, polyamide and wool). The qualitative assays were performed through two methodologies: Inhibition Halo (HZ) and Inhibition of Surface (Print). The carpet with the product inhibited 100% of bacterial (Staphylococcus aureus) and fungi (Aspergillus niger) growth, under the conditions of this study. The microbial inhibition was higher in upper portion of carpets. The methodologies employed appear to be adequate to test the bactericide and fungicide activities of the Tri-N-Butyl Tin maleate. The print methodology confirmed the results obtained by the inhibition zone assay. Further studies using the same methodologies are needed to confirm our results. O objetivo do presente estudo foi verificar a atividade do composto maleato de estanho tri-n-butílico contra Staphylococcus aureus e Aspergillus niger, após sua aplicação industrial em 40 amostras de carpetes de diferentes materiais (polipropileno, poliéster, poliamida e lã). Os ensaios qualitativos foram realizados através de duas metodologias: Zona de Inibição (ZI) e Superfície de Inibição (Impressão). Os carpetes tratados com o produto apresentaram 100% de inibição de crescimento bacteriano (Staphylococcus aureus) e fúngico (Aspergillus niger), sob as condições desse estudo. A inibição de crescimento microbiano foi mais elevada na porção superior dos carpetes. As metodologias empregadas parecem ser adequadas para testar a atividade bactericida e fungicida do maleato de estanho tri-n-butílico. A metodologia de impressão confirmou os resultados obtidos no ensaio de zona de inibição. Estudos futuros utilizando as mesmas metodologias são necessários para confirmação destes dados.